Ultrafiltrazione peritoneale e sindrome cardiorenale: gestione del sovraccarico di fluidi e ruolo del sodio - Luca Di Lullo; Claudio Ronco; Fulvio Floccari; Antonio De Pascalis; Rodolfo Rivera; Antonio Granata; Antonio Bellasi (AboutScience Srl, 2019)
Congestion represents a crucial clinical component of both heart failure and cardiorenal syndrome and it has been postulated to modulate heart and kidney cross-link. Diuretic therapy is a corner stone in the treatment patients with heart failure, and renal replacement therapies are mainly used for patients with refractory heart failure who have not reached the worst stages of renal disfunction. Peritoneal dialysis is a home-based therapeutic modality providing both solute clearance and ultrafiltration, together with relief from congestion in decompensated heart failure patients. The following review will focus on sodium removal in refractory decompensated heart failure patients undergoing peritoneal dialysis. (Cardionephrology)